Acute lymphadenopathy complicating quinidine therapy. Issue 775 (May 1990) - Lau, C. P.; Wong, K. L.; Wong, C. K.; Leung, W. H.
Abstract : A patient is described with quinidine-induced acute lymphadenopathy syndrome proven by rechallenge of the drug. Serum markers for systemic lupus were negative.